Analysis of network public opinion on COVID-19 epidemic based on the WSR theory - Yang, Kun; Zhu, Junqi; Yang, Li; Lin, Yu; Huang, Xin; Li, YunPeng (Frontiers in Public Health, 2023)
Objective: To obtain the influencing factors of public opinion reactions and to construct a basic framework of the factors of the occurrence of online public opinion in the epidemic area. Methods: The hot news comments on microblogs during the epidemic in Shanghai were collected and analyzed with qualitative analysis, grounded theory, and the "Wuli-Shili-Renli" (WSR) methodology as an auxiliary method. Results:1) Three core categories of the Wuli system, the Shili system, and the Renli system, 15 main categories, and 86 categories that influence the development of online public opinion are obtained.2) WSR Elements Framework of Network Public Opinion (WSR-EFONPO) is established. 3) The WSR-EFONPO is explained. Conclusion: The framework of factors for the occurrence of online public opinion is proposed, and the development process of online public opinion under COVID-19 is sorted out, which is of great theoretical value in guiding the public in the epidemic area to form a reasonable behavior.